Easy characterization of the etched Al5052 surfaces and its distinctive data correlation with the Al5052/PMMA bonding performance. (August 2022) - Li, Jiajin; Cheng, Pu; Zhang, Ruizhi; Liu, Zhiqiang; Luo, Guoqiang; Sun, Yi; Zhang, Jian; Tu, Rong; Wang, Chuanbin; Shen, Qiang
Abstract: Pore–creating of the metal surface is essential to the bonding performance of the metal/polymer laminate interface. This work made use of the high distinction of the mass variation and surface porosity (SP) values of every etched 5052 aluminum alloy (Al5052) sheet to characterize the porous surface, in order to set up distinctive data correlations between surface characterization and bonding performance of the Al5052/polymethyl methacrylate (PMMA) laminate. The obtained distinctive characterization–performance correlations indicate that in certain scattered plots regions (mass variation: 0–2.5%; SP: 0–25%/dm 2 or 0–32%/cm 3 ), parabola relations existed between the mass variation/SP and the bonding strength (BS), and linear relations existed between the mass variation/SP and the interface failure work (IFW), which was corroborated by analysis on a simplified springs model. In the discrete regions, the distinctive characterization–performance correlations also showed that the BS was limited between 6.25 and 8.25 MPa and the IFW fluctuated between 346 and 691 mJ/cm 2 . According to the data correlations, the SP limit of Al5052 in this work was 70%/dm 2, which could help determine and control the degree of surface treatment. Graphical Abstract: ga1 Highlights: Distinctive data were applied to easily characterize the etched Al5052 surfaces. Bonding performances were thoroughly correlated with the as-characterized data. Equivalent springs model was proposed to vividly explain the fitted regions. Bonding performance limits were charted out by data-performance correlation.